Arahan Pencegahan Bencana Banjir Pada Perumahan Di Kawasan Sub Urban Kota Makassar - Utari Nur Parmadi; Mimi Arifin; Mukti Ali (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2022)
Tamalanrea Indah Village is one of the areas that has been designated as a flood-prone area based on data from the RTRW of Makassar City in 2015-2034. The research aims to determine the physical characteristics of the area, the factors that cause flooding, and formulate prevention of flood hazards. Data was collected by using observation, questionnaire, interview and literature study techniques. This research is included in a quantitative qualitative descriptive study conducted. The data collection method was carried out primarily through surveys, interviews, questionnaires and documentation. Secondary data obtained from literature studies and visits to institutions. The analytical technique used in this research is spatial analysis (overlay) to identify the physical condition of the area at the research location. Then to determine the factors causing flooding at the research site using AHP analysis with the help of qualitative and quantitative descriptive analysis and hydrological analysis to determine the factors causing flooding. The results of this study are recommendations for preventing flood hazards in Hamzy BTN. The research was carried out as an effort to avoid flooding in the Makassar City sub-urban, especially in Hamzy BTN, Tamalanrea Indah Village, Tamalanrea.